Perceived Influence of Work Stress on Health of Public Secondary School Teachers in Irele Local Government Area of Ondo State, Nigeria - Igudia, E. O.; Oronsaye, D. O.; Owombo, H. O. (NIU Journal of Social Sciences; Vol 5 No 2 (2019): KIU Journal of Social Sciences, Vol. 5 No. 2, June 2019, 2019)
The purpose of the study was to determine the relationship between perceived influence of work stress on physical, mental, emotional and social health of secondary school teachers in Irele Local Government Area of Ondo State. In order to effectively carry out the study to achieve this aim, four hypotheses were formulated to guide the study. The survey research design was employed for the study and the population consisted of all the 292 secondary school teachers in the 10 public schools in the area of study. The sample size was 200 and was selected through the 2-stage sampling procedures. Data were collected through a self-made questionnaire designed by the researchers on perceived influence of work stress on physical, mental, emotional and social health of secondary school teachers in the study area. The data were later analysed using descriptive statistics of frequency counts and percentages as well as inferential statistics of chi-square. The results of the study among others revealed that: there is a significant relationship between perceived influence of work stress on physical (p≤0.05), mental (p≤0.05), emotional ((p≤0.05) and social health (p≤0.05) of secondary school teachers in Irele Local Government Area of Ondo State. Based on the findings, the researchers concluded that stress has negative impacts on the health of secondary school teachers in Irele Local Government Area of Ondo State.  Following this, it was recommended among others that government at all levels should employ more academic staff in order to reduce teachers’ stress and also, teachers should be educated on various stress coping and managerial skills in order to enhance their overall wellbeing. Key Words : influence, perception, work stress, health